2010
DOI: 10.1038/ajh.2009.245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exenatide on Systolic Blood Pressure in Subjects With Type 2 Diabetes

Abstract: These results support the need for a prospective, randomized, controlled study of BP changes during exenatide treatment in patients with hypertension and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 34 publications
4
131
0
3
Order By: Relevance
“…Animal studies showed their antihypertensive and natriuretic effects. [48][49][50] In humans, treatment of type 2 diabetic patients with these drugs was associated with improvement of systolic blood pressure, 51 and improvement of endothelial function, independent of the improvement of insulin sensitivity. 52 The precise mechanisms underlying the reported effects of incretin mimetics on cardiovascular system are not fully clear as yet.…”
mentioning
confidence: 99%
“…Animal studies showed their antihypertensive and natriuretic effects. [48][49][50] In humans, treatment of type 2 diabetic patients with these drugs was associated with improvement of systolic blood pressure, 51 and improvement of endothelial function, independent of the improvement of insulin sensitivity. 52 The precise mechanisms underlying the reported effects of incretin mimetics on cardiovascular system are not fully clear as yet.…”
mentioning
confidence: 99%
“…In a small double blind placebo controlled pilot study of normotensive type two diabetic individuals, exenatide lowered the systolic blood pressure with no effect on both the diastolic blood pressure and the heart rate [31]. Okerson et al conducted a larger study with longer duration that also showed the ability of exenatide to reduce the systolic blood pressure as compared to placebo and insulin.…”
Section: Glp1 and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Exenatide elicits a significant improvement in glycemic control, including postprandial glucose concentration, 35,36 and many patients treated with exenatide experience significant weight loss. [37][38][39][40][41][42] Furthermore, exenatide has also shown to have a positive effect on blood pressure in hypertensive patients, 37,38,43 but there are no consistent trends in regards to exenatide's effect on lipids. [44][45][46][47][48] Numerous studies have compared exenatide to placebo [49][50][51][52] or insulin 47,[53][54][55] in patients receiving metformin and/or sulfonylureas.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…However, mean systolic blood pressures were near target level 71 of ,130 mmHg (mean of 130 mmHg and 133 mmHg) and mean diastolic levels were below the 80 mmHg target (mean 75 mmHg and 76 mmHg); blood pressure outcomes were not reported by baseline blood pressure. A recent meta-analysis of clinical trial data, as discussed above, found that blood pressure reduction appears to occur in patients with elevated blood pressure but not necessarily in normotensive patients, 43 which may help explain why an effect on blood pressure was generally not observed in exenatide retrospective analyses.…”
Section: Retrospective Outcomes Analysesmentioning
confidence: 99%